Healthcare workers issues and COVID-19 pandemic: a review - Abd Rahman, Anita; Muhamad Saliluddin, Suhainizam; Rusli, Mohammad Farhan; Pakar Singh, Param Jeeth Singh; Mohd Rosli, Norazman; Shah, Shamsul Azhar (Gazi University Medical Faculty, 2020)
Background: Since December 2019, COVID-19 pandemic has continued to grow it spread and has currently affected more than 200 countries and for the last four months, healthcare workers (HCW) has worked performed their duties endlessly, more than the norms at their respective health care facility. Therefore this review paper aims to describe healthcare workers issues in managing the current COVID-19 pandemic Materials and Methods: Articles were chosen using a structured search via three electronic databases, namely PubMed, Scopus, and Direct Science coupled with a combination of keywords namely "healthcare workers" OR "health staff" AND "COVID19". Other inclusion criteria include full accessible, original studies in English language, published in peer-reviewed journals from December 2019 till 30th April 2020. Result and Discussion: A total of 17 articles were chosen to be reviewed which can be further broadly categorised into three domains which are; physical effects, psychological effects and socioeconomic effects. COVID-19 infection among healthcare workers is not uncommon as they represent the essential human resources in managing the pandemic. Of the three effects, mental health burden ranging from anxiety to burnout was studied along with its risk and protective factors discussed. Socioeconomic factors describe how prevention and control measures adopted has given a toll to this vulnerable group. Conclusion: Health-related effects and unforeseen factors has impacted healthcare workers such as the direct effect of the infection, issues related to the use of personal protective equipment, the spectrum of mental health burden as well as the socio-economic effects as a result of the demands faced by them in responding and providing healthcare needs.